Data mining of motor patterns recorded with wearable technology. - Bonato, P.
Discusses utilizing self-organizing maps to manage large data sets gathered in the field. Dramatic advances in wearable technology suggest that wearable sensors and systems are close to deployment in the clinical field environment. Miniature, wireless sensors are becoming readily available due to the tremendous research efforts focused on this area as well as the great interest demonstrated by the private sector for the associated potential market of these devices. Wearable systems, including base stations and hand-held units, are becoming less cumbersome, with an ever-increasing capacity to receive and store vast amounts of data for extensive periods of time. Further, the growing availability of wireless LANs makes it possible to envision wearable systems from which data can be continuously uploaded, while hand-held units provide a means to communicate with the patient when needed.
Keywords: Base stations; Continuously uploaded data; Hand-held units; Medical instrumentation; Motor patterns recorded with wearable technology; Patient communication; Wearable sensors; Wearable technology advances; Wireless LANs